2005
DOI: 10.1518/0018720053653884
|View full text |Cite
|
Sign up to set email alerts
|

Interruption Management: The Use of Attention-Directing Tactile Cues

Abstract: Previous research has suggested that providing informative cues about interrupting stimuli aids management of multiple tasks. However, auditory and visual cues can be ineffective in certain situations. The objective of the present study was to explore whether attention-directing tactile cues aid or interfere with performance. A two-group posttest-only randomized experiment was conducted. Sixty-one participants completed a 30-min performance session consisting of aircraft-monitoring and gauge-reading computer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…Several studies have demonstrated the usefulness of tactile information input in multi-task situations (Hopp, Smith, Clegg, & Heggestad, 2005;Sarter, 2002Sarter, , 2001Sklar & Sarter, 1999;Van Erp, 2001;. Tactile systems have proved particularly effective when other information channels are overloaded or distorted (e.g., auditory channel in a noisy environment; visual channel when visibility is low).…”
Section: Multiple Resource Theorymentioning
confidence: 99%
“…Several studies have demonstrated the usefulness of tactile information input in multi-task situations (Hopp, Smith, Clegg, & Heggestad, 2005;Sarter, 2002Sarter, , 2001Sklar & Sarter, 1999;Van Erp, 2001;. Tactile systems have proved particularly effective when other information channels are overloaded or distorted (e.g., auditory channel in a noisy environment; visual channel when visibility is low).…”
Section: Multiple Resource Theorymentioning
confidence: 99%
“…In order to improve user performance it has been suggested the use of cues signaling when the secondary task requires attention [17]. This suggests that providing an external mnemonic may greatly benefit performance for people who deal with safety critical interruptions and prospective memory tasks.…”
Section: Surviving Interruptionsmentioning
confidence: 99%
“…Current literature about interruptions in human computer interaction addresses this problem from one the following different perspectives: a) psychology of human interruption [29]; b) technologies for improving the quality of interruption generation [23]; c) HCI methods for brokering interruptions [17]; d) the effects of interruptions in work settings [28]; and e) case studies describing the results of introducing technologies into the workplace in an attempt to improve coordination performance [25].…”
Section: Introductionmentioning
confidence: 99%
“…Tactile interfaces have even been used to support the orientation awareness of astronauts in micro-gravity environments (van Erp & van Veen, 2000). A growing number of studies have also started to investigate the potential for using tactile displays to provide route finding information to travelers van Erp, van Veen, Jansen, & Dobbins, 2005; see also Nagel, Carl, Kringe, Martin, & Konig, 2005), to improve the perception and composition of music (Gunther & O'Modhrain, 2003), to cue driver attention in vehicular settings (e.g., Ho, Tan, & Spence, 2005, 2006Lee, Hoffman, & Hayes, 2004), to provide silent alerts to mobile phone users (Brown & Kaaresoja, 2006;Brown, Brewster, & Purchase, 2006b), and/or to manipulate a user's visual attention in a variety of multisensory task settings (e.g., Gray & Tan, 2002;Hopp, Smith, Clegg, & Heggestad, 2005;Hopp-Levine, Smith, Clegg, & Heggestad, 2006;Tan, Gray, Young, & Traylor, 2003).…”
Section: Tactile Processing Across the Body Surfacementioning
confidence: 99%